2020
DOI: 10.3389/fnins.2020.00642
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Neurite Spine Loss Induced by Dopamine D2 Receptor Overactivation in Striatal Neurons

Abstract: Psychosis has been considered a disorder of impaired neuronal connectivity. Evidence for excessive formation of dopamine D2 receptor (D2R)-disrupted in schizophrenia 1 (DISC1) complexes has led to a new perspective on molecular mechanisms involved in psychotic symptoms. Here, we investigated how excessive D2R-DISC1 complex formation induced by D2R agonist quinpirole affects neurite growth and dendritic spines in striatal neurons. Fluorescence resonance energy transfer (FRET), stochastic optical reconstruction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…However, the effects of DRD2 and the PI3K pathway on electrophysiological activity in the TNC in CM rats have not been explored, which is a limitation of this study and will be our focus in future studies. In addition, we used NMDA instead of AMPA to establish the model of neuronal excitation [ 32 ] taking into account the neurotoxicity mediated by AMPA [ 61 ] and the observation that NMDA can also induce the increased expression of GLUA1-containing AMPARs on the membrane surface of neurons, which is pertinent to the purpose of this study [ 18 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effects of DRD2 and the PI3K pathway on electrophysiological activity in the TNC in CM rats have not been explored, which is a limitation of this study and will be our focus in future studies. In addition, we used NMDA instead of AMPA to establish the model of neuronal excitation [ 32 ] taking into account the neurotoxicity mediated by AMPA [ 61 ] and the observation that NMDA can also induce the increased expression of GLUA1-containing AMPARs on the membrane surface of neurons, which is pertinent to the purpose of this study [ 18 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has proven that DRD2 can modulate the firing of spinal neurons and thus alleviate pain behavior in neuropathic pain models [ 15 17 ]. An in-vitro study proved that DRD2 can regulate the dendritic density and dendritic spine morphology in striatal and hippocampal neurons [ 18 , 19 ]. In addition, several studies have reported that DRD2 can regulate the phosphorylation of the AMPA receptor [ 20 ] and alleviate AMPA receptor-mediated neurotoxicity [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This peculiar interaction could represent a potential D2R-mediated unconventional MOA at the dopamine receptor. In contrast, uncoupling D2R-DISC1 interaction, through the trans-activator of transcription (TAT)-D2pep (TAT-D2pep), reduced the previously discussed effect, resulting in a neuroprotective and preventive effect for neurite outgrowth and dendritic spines by associating with the downregulation of synaptophysin and PSD-95 expression [ 369 ].…”
Section: Resultsmentioning
confidence: 99%